Vaginal delivery at term with previous one cesarean section: is it safe? - Bera, Surendra N.; Sharma, Partha P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Post cesarean pregnancies are high risk pregnancy and main concern is uterine scar rupture with increasing maternal and perinatal risks, for vaginal birth after cesarean delivery (VBAC). Objective of this study is to know neonatal and maternal outcome at term who attempt vaginal delivery with previous one cesarean section presenting in active stage of labor. Methods: A total of 277 pregnant women with single live fetus at term, cephalic presentation with previous one cesarean section, underwent a trial of labor and outcome of successful and failed vaginal birth were noted. Results: Trial of labor was successful in 52.3% and failed in 47.7% (p=0.269). VBAC was successful where the previous cesarean section indications were fetal distress (79% versus 21%, p=0.000), pregnancy induced hypertension (77.3% versus 22.7%, p=0.000) and fetal growth restriction (81.8% versus 18.2%, p=0.000), when compared with failed trial of labor who required emergency cesarean section in pre-labor rupture of the membranes (8.3% versus 91.7%, p=0.000) and dystocia (3.3% versus 96.7%, p=0.000). VBAC was successful at gestational age of 37 0/7-38 6/7 weeks (p=0.000). In the failed VBAC women who required emergency cesarean section there was significant early neonatal death (p=0.025). Scar dehiscence and hospital stay with or without complications were more in the failed VBAC group. Conclusions: Early neonatal death and duration of hospital stay were significantly more in the failed VBAC, who were posted for emergency cesarean delivery. Scar dehiscence occurred in the failed VBAC group. Women presenting at 37 0/7 to 38 6/7 weeks of gestation with cephalic presentation in active stage of labor who had previous cesarean section done for fetal distress, pregnancy induced hypertension and fetal growth restriction with inter pregnancy interval of > 24 months can be planned and counselled for VBAC trial of labor.